2014
DOI: 10.1007/s10926-014-9555-0
|View full text |Cite
|
Sign up to set email alerts
|

Construct Validity of Functional Capacity Evaluation in Patients with Whiplash-Associated Disorders

Abstract: Purpose The construct validity of functional capacity evaluations (FCE) in whiplash-associated disorders (WAD) is unknown. The aim of this study was to analyse the validity of FCE in patients with WAD with cultural differences within a workers’ compensation setting. Methods 314 participants (42 % females, mean age 36.7 years) with WAD (grade I and II) were referred for an interdisciplinary assessment that included FCE tests. Four FCE tests (hand grip strength, lifting waist to overhead, overhead working, and r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
13
0

Year Published

2017
2017
2019
2019

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 13 publications
(14 citation statements)
references
References 45 publications
1
13
0
Order By: Relevance
“…Both studies found differences in FCE performance associated with participant's mother language groups in the German canton of Switzerland (German and non-German) and United States (English and non-English). The study comparing primary German and non-German language speakers evidenced that the German-speaking group performed consistently higher on all FCE tests included in the study, i.e., handgrip strength, waist-tooverhead lift, and overhead work and repetitive reaching task [29]. The study comparing primary English and non-English language speakers evidenced that the English-speaking group showed a moderately higher percentage of valid performance effort (70.2%), with respect to the non-English-speaking group (27.3%) [28].…”
Section: Patientsmentioning
confidence: 86%
See 4 more Smart Citations
“…Both studies found differences in FCE performance associated with participant's mother language groups in the German canton of Switzerland (German and non-German) and United States (English and non-English). The study comparing primary German and non-German language speakers evidenced that the German-speaking group performed consistently higher on all FCE tests included in the study, i.e., handgrip strength, waist-tooverhead lift, and overhead work and repetitive reaching task [29]. The study comparing primary English and non-English language speakers evidenced that the English-speaking group showed a moderately higher percentage of valid performance effort (70.2%), with respect to the non-English-speaking group (27.3%) [28].…”
Section: Patientsmentioning
confidence: 86%
“…There was moderate quality of evidence that higher previous job salary was significantly associated with larger distance walked in the 6MWT [25]. There was low or very low quality of evidence that patients not involved in compensation [19,21] and/or litigation [19] processes, and healthy participants tested after a day's work [24] performed significantly better on FCE tests; also, patients with differences in the instruction [27] and in their primary or mother language [28,29], and both patients and healthy participants with different ethnicity [28,31], had significantly different FCE performances. There was an absence of association of workplace social support reported by patients and healthy participants [22,26] and the different environmental conditions, in which FCE was undertaken [20], with FCE performance.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations